Energy conversion on the flow induced vibration - Kalfian, Jo (2013)
Currently the fossil fuel reserves have been depleted rapidly, and hence a sustainable energy resource is being sought in order to cover the energy demand globally. Vortex Induced Vibration (VIV) is one type of clean energy, which is a new concept in the power generating system. This concept could be used to generate kinetic power from fluid flows in oceans, rivers and stream. Hydrokinetic energy, for instance, from the flow of water is ubiquitous worldwide in the form of waves, currents, and tides; therefore it is easy and viable to get a clean energy.